Probability of a successful platelet dose according to the number of platelet concentrates - Llaca Díaz, Jorge Martín; Robles Espino, Diana Guadalupe; Díaz Chuc, Erik A.; De la Rosa López, Alejandro; Ayala de la Cruz, Sergio (2022)
Introduction: Platelet transfusion for prophylactic or therapeutic purposes is a common practice. The outcome evaluated in using platelets for prophylactic purposes has been preventing clinically significant bleeding. Transfusion guidelines recommend using platelet transfusion for prophylactic purposes based on the clinical scenario and a peripheral blood platelet threshold.